Giardia and Vilem Dusan Lambl - Lipoldová, M. (Marie) (PLoS Neglected Tropical Diseases, 2014)
Giardiasis is a neglected disease, which spreads worldwide from Arctic to Tropics. It affects nearly 2% of adults and 6% to 8% of children in developed countries worldwide. Nearly 33% of people in developing countries have had giardiasis. The disease is caused by a binucleated flagellated protozoan parasite Giardia lamblia (syn. G. intestinalis, G. duodenalis) that inhabits the small intestine in humans and the other mammals. Clinical giardiasis is varied and ranges from asymptomatic passage of cysts to abdominal cramps, nausea, acute or chronic diarrhea, malabsorption, weight loss, and failure of children to thrive in both subclinical and symptomatic disease. The first description of Giardia had been attributed to Antonie van Leeuwenhoek, who in his letter to the Royal Society in November 4, 1681 described presence of microorganisms in his stool. However, the first microscopic drawing of morphological characteristics identifying the parasite Giardia, was provided by Vilém Dušan Lambl in 1859 analysing stool of a child. V. D. Lambl is also famous for describing Lambl's excrescences (1856) and for introducing detection of bladder cancer using the analysis of cells present in urine (1856).